Assessing the Impact of “Belajar Membaca Lancar” and “Membaca Bersama Budi” Applications on Early Reading Proficiency: A Comparative Study - Windi Maudia; Muhamad Taufik Hidayat (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the effectiveness of the application of Belajar Membaca Lancar and Membaca Bersama Budi on improving early reading skills and whether or not there are differences in learning outcomes of the two applications. This type of research uses comparative research with a quasi-experimental design. The data collection technique uses tests, observations, and documentation. The data analysis technique used Independent Sample t-test and Gained Score. The results of this study were that learning to read beginning with the application media for Belajar Membaca Lancar was more effective. It is proven by the comparison value of n gain of the two applications was 1.25641 1. In this study, there was no difference in the results of the two applications with a calculation of 0.50 0.05. It showed that the two applications, namely Belajar Membaca Lancar and to Membaca Bersama Budi, could be applied as an alternative learning media to improve the initial reading ability of students.